2016
DOI: 10.1371/journal.pone.0168729
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Location of Medical Emergency Team Activation Is Associated with Seriousness of Outcome: An Observational Study in a Tertiary Care Hospital

Abstract: PurposeThe medical emergency team (MET) can be activated anytime and anywhere in a hospital. We hypothesized the timing and location of MET activation are associated with seriousness of outcome.Materials and MethodsWe tested for an association of clinical outcomes with timing and location using a university hospital cohort in Japan (n = 328). The primary outcome was short-term serious outcome (unplanned ICU admission after MET activation or death at scene).ResultsPatients for whom the MET was activated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Mortality was significantly higher during the night shift than during the day shift. Taking the high mortality rate in the night shift, which has been previously reported, 11 into consideration, different approaches to increase RRT/MET calls during the night shift are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality was significantly higher during the night shift than during the day shift. Taking the high mortality rate in the night shift, which has been previously reported, 11 into consideration, different approaches to increase RRT/MET calls during the night shift are needed.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although there are many reported studies of RRS in the world, very few have been reported from Japan; of these, most were reported from a single institution. [8][9][10][11][12] Therefore, detailed information with regard to Japanese epidemiological data for in-hospital emergencies is not available. In February 2014, the In-Hospital Emergency Registry in Japan (IHER-J), a multicenter RRS online registry, was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…who required immediate medical attention within the hospital grounds. All hospital staff could activate the RRS code in response to pre-defined criteria [13,14].…”
Section: Ecpr Ecmo and Rrsmentioning
confidence: 99%
“…An earlier observational study has demonstrated MET team activations in the evening or night-time to be associated with significantly higher short-term serious outcomes such as unplanned ICU admission and death. 9 An Australian-based retrospective observational study demonstrated that 53% of hospital-wide MET activations occurred out of peak staffing hours. 10 Our lower after hours incidence can be attributed to patient selection and the types of procedures performed.…”
Section: Discussionmentioning
confidence: 99%